THE Implementation and Analysis of Internet Networking Monitoring System with Hillstone Hardware at Indonesian Christian University - Lumbantoruan, Rutman (Fundamental Management Journal, 2020)
Computer Internet Network Monitoring is a computer system managing activity connected to many servers in an organization. This monitoring system is used to help adjusting and monitoring server network continuously. Internet connection monitoring has benefit in bandwidth usage monitoring for every user, either it is being used or not. Network monitoring is created by installing Hillston Hardware in Information System Implementation Unit. A trouble usually happened when slow loading time occurred in online registration hence error network in consequence. A result obtained after Hillstone Hardware implementation is centre of data staffs could detect network trouble and simplify its handling. Hillstone is reliable to monitor undergoing internet data services in user and network, also activates warning system to user connecting to improper internet network or bandwidth. Keywords: Monitoring, Internet connection analysis, Hillstone, server, bandwidth